Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women - Garan Jones (Nature Portfolio, 2021)
Muscle weakness has been associated with morbidity and mortality in older people. Here, the authors have investigated this trait further by performing a genome-wide meta-analysis of grip strength and Mendelian randomization to discover causal relationships between muscle weakness and other diseases.